(untitled) (Research, Society and Development, 2020)
The World Health Organization defines lifestyle as the set of habits and customs that are influenced, modified, encouraged or inhibited by the prolonged socialization process. On the other hand, health promotion is anchored in the trinomial integrality, health-disease and care. Objective: To analyze the interfaces between lifestyle and health promotion of university professors. Methodology: quantitative, descriptive study, carried out in a public higher education institution located in a municipality in the State of Rio de Janeiro. The Questionnaire called Fantastic Lifestyle was applied to apprehend lifestyles and the analysis was used by descriptive statistics by the Excel program. Results: The population is composed mostly of women, aged around 50 years, with an average time of 16 years, married and without children. The teaching population presented "Behavior with health and sexual and other behaviors" as the healthiest; the domain "Work and type of behavior" what needs to improve and the domain "Physical activity" the Identify work at the university as a stressing factor of importance, but report being able to control stress in their daily work. They are sensitive to health promotion actions and are therefore attentive to feelings of haste and tension, and there are positive thoughts of a pleasurable work.